2007
DOI: 10.1111/j.1365-294x.2007.03336.x
|View full text |Cite
|
Sign up to set email alerts
|

Introduction history of Drosophila subobscura in the New World: a microsatellite‐based survey using ABC methods

Abstract: Drosophila subobscura is a Palearctic species that was first observed in South and North America in the early 1980s, and that rapidly invaded broad latitudinal ranges on both continents. To trace the source and history of this invasion, we obtained genotypic data on nine microsatellite loci from two South American, two North American and five European populations of D. subobscura. We analysed these data with traditional statistics as well as with an approximate Bayesian computation (ABC) framework. ABC methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
190
2
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(202 citation statements)
references
References 61 publications
9
190
2
1
Order By: Relevance
“…Although, SSR motifs with more than five repeats were considered here, shorter SSRs were identified. The maximum length achieved was 16 repeats; this is consistent with studies that revealed shorter SSRs in Drosophila [26,27]. …”
Section: Discussionsupporting
confidence: 89%
“…Although, SSR motifs with more than five repeats were considered here, shorter SSRs were identified. The maximum length achieved was 16 repeats; this is consistent with studies that revealed shorter SSRs in Drosophila [26,27]. …”
Section: Discussionsupporting
confidence: 89%
“…Genetic variation was summarized within and between populations, using the following statistics: the F ST values between pairs of populations (Weir and Cockerham, 1984) and the mean individual assignment likelihoods of individuals collected in population i and assigned to population j (L i-j , Pascual et al, 2007), the mean number of alleles per locus, the expected heterozygosity (H, Nei, 1987) and the mean variance of the absolute allelic size (V, Estoup et al, 2004) computed for each population (A, H, V) or for each pair of populations (that is by pairwise pooling of population samples) (A2P, H2P and V2P). The default set of statistics (hereafter referred to as 'default stat') was A2P, H2P, V2P, F ST values and L i-j and hence 'Miller' and 'Beaumont stat' to select the best set of summary statistics.…”
Section: Summary Statisticsmentioning
confidence: 99%
“…Such flat posterior probabilities should, therefore, be interpreted with caution, as they may indicate errors in parameter priors and/or model specification. The comparison between observed summary statistics and simulated statistic distributions may also be used to detect such errors (Pascual et al, 2007). In practice, one could advise ABC users to (i) choose broad support of priors (that is region of the prior with positive probabilities) to ensure that it includes the 'true values' of parameters, (ii) be sceptical about prior distributions and/or model specifications when obtaining low maximal probabilities with large 95% CI and (iii) compare the results obtained with and without the unsampled and the inverse-serial scenarios to be able to detect error in scenario specifications.…”
Section: T Guillemaud Et Almentioning
confidence: 99%
See 2 more Smart Citations